The effects of low pH and CO2 on bovine corneal lactate production - Sarroca, A; Lin, S; Bonanno, J A (The CLAO journal, 1997)
Hypoxic corneal swelling in human subjects is reduced by CO2 induced corneal acidosis. We investigated whether this effect could be explained by a reduction in lactate production under acidic conditions. Lactate production from isolated bovine corneas was assayed under normoxic and hypoxic conditions at normal pH (7.5) and low pH (7.05). Low pH was achieved using a CO2/HCO3- Ringer or a HEPES buffered Ringer. Normoxic corneas produced significantly less (approximately 25%) lactate under all acidic conditions. In contrast, hypoxic corneas produced the same or slightly less lactate under acidic conditions (weighted average of all conditions = 6% less lactate). From these results, we concluded that pH can have a substantial effect on lactate production, but its influence on glycolytic activity during hypoxia is suppressed and may be negligible.